2021
DOI: 10.4102/sajim.v23i1.1361
|View full text |Cite
|
Sign up to set email alerts
|

The impact of outsourcing information technology services on business operations

Abstract: Background: Organisations outsource Information Technology (IT) services in order to keep up with the IT evolution and to remain competitive. Although the IT operations department is responsible to manage service provider service quality, they are not in a position to evaluate IT services performance because of the loss of control and capability in the IT environment.Objectives: This article investigated the impact of outsourcing in-house IT services on the performance of IT operations and how it affects the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…Concerning outsourcing information technology, prior research (Pankowska, 2019;Mtsweni, et al, 2021) discussed the advantages and disadvantages of outsourcing information technology. The advantages of information technology outsourcing involve easier access to technical experts and programmers and no need for recruiting highly technical human resources.…”
Section: Analysis Of Internal Auditors' Role In the Era Of Blockchain...mentioning
confidence: 99%
See 3 more Smart Citations
“…Concerning outsourcing information technology, prior research (Pankowska, 2019;Mtsweni, et al, 2021) discussed the advantages and disadvantages of outsourcing information technology. The advantages of information technology outsourcing involve easier access to technical experts and programmers and no need for recruiting highly technical human resources.…”
Section: Analysis Of Internal Auditors' Role In the Era Of Blockchain...mentioning
confidence: 99%
“…The advantages of information technology outsourcing involve easier access to technical experts and programmers and no need for recruiting highly technical human resources. On the other hand, outsourcing information technology means losing control of the IT process (Mtsweni, et al, 2021). In addition, outsourcing might result in the loss of organizations' valuable and confidential information, as a result of equipment theft or information security breaches, or lack of commitment from the service provider's side Mtsweni, et al, 2021) that might put the company at risk and might expose the company to the risk of service provider failure (Pankowska, 2019).…”
Section: Analysis Of Internal Auditors' Role In the Era Of Blockchain...mentioning
confidence: 99%
See 2 more Smart Citations
“…All that based on the results of interviewing three organizations in the UAE (Hani Al-Kassem, 2021;Straub et al, 2008). According to (Muhammad Turki Alshurideh et al, 2023c;Mtsweni et al, 2021), few papers looked at outsourcing relationships from both clients and vendors viewpoints. (Al-Kassem, 2017;Kalbasi et al, 2021;) also suggested that using the viewpoint of some other stakeholders as well like IT and business managers or staff would provide some new ideas (Rimba et al, 2020).…”
Section: Introductionmentioning
confidence: 99%